Key workers in Ghana during the COVID-19 pandemic - Akosua Keseboa Darkwah (International Labour Organization (ILO), 2022)
This study analyses the experience of key workers in Ghana during the COVID-19 pandemic. It analyses their working conditions prior to the pandemic, and then assesses how the pandemic heightened their job demands. In addition, it assesses the extent to which the State and private employers provided the requisite job resources to enable them to cope with the increased demands caused by the crisis. The study finds that some frontline workers have had an increase in work pressure, while other categories of workers, particularly in the informal economy, experienced a decrease in work pressure as demand for their services fell off given the general declines in income. The study finds that although the pandemic reshaped the work environment, workers' concerns regarding the future were not tied directly to concerns about COVID-19, but rather to larger concerns about working conditions and income security that existed prior to the crisis.
Keywords: 330; workers; working conditions; COVID-19